Effects of recurrent selection for grain yield and Striga resistance in an extraearly maize production - Badu-Apraku, Baffour (Wiley, 2010)
Striga hermonthica (Del.) Benth threatens maize (Zea mays L.) production in sub-Saharan Africa. In an extra-early population, S1 families derived from four cycles of recurrent selection for grain yield and Striga resistance were evaluated with and without Striga infestation at three locations in Nigeria for 2 yr to determine relative changes in genetic variances, heritabilities, and genetic correlations for yield and other traits. Under infestation, yield was not correlated with other traits at C0 but was significantly correlated with ears per plant (EPP), Striga damage, and emerged Striga plants in advanced cycles. Genetic correlations between yield and most traits were significant in C0 when Striga-free but was reduced in advanced cycles. Genetic variances and heritabilities for yield and ear aspect increased in advanced cycles. Genetic variances decreased with selection for emerged Striga counts and EPP under infestation. A response to selection for improved yield, Striga emergence and EPP is expected in subsequent cycles. Low genetic variances and heritabilities for Striga damage and low predicted gain cycle−1 for all traits except numbers of emerged Striga plants suggest a need to introgress novel resistance genes into the population for faster progress from selection for increased yield.